2020
DOI: 10.1038/s41398-020-01024-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated phosphoproteomic and metabolomic profiling reveals perturbed pathways in the hippocampus of gut microbiota dysbiosis mice

Abstract: The dysbiosis of gut microbiota is an important environmental factor that can induce mental disorders, such as depression, through the microbiota–gut–brain axis. However, the underlying pathogenic mechanisms are complex and not completely understood. Here we utilized mass spectrometry to identify the global phosphorylation dynamics in hippocampus tissue in germ-free mice and specific pathogen-free mice (GF vs SPF), fecal microbiota transplantation (FMT) model (“depression microbiota” and the “healthy microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…Interestingly, AQR, LSM3, BUD31, SART1 and SF1 are important components of spliceosome that catalyzes the pre-mRNA splicing. The downregulations of these spliceosome related proteins in GF mice comparted with the SPF mice, suggesting the inhibition of pre-mRNA alternative splicing, this findings was consistent with that of our previous study focused on the phosphorylation modification changes in the hippocampus of GF mice [30].…”
Section: Functional Analysis Of Differentially Expressed Proteins In the Absence Of Gut Microbiotasupporting
confidence: 92%
“…Interestingly, AQR, LSM3, BUD31, SART1 and SF1 are important components of spliceosome that catalyzes the pre-mRNA splicing. The downregulations of these spliceosome related proteins in GF mice comparted with the SPF mice, suggesting the inhibition of pre-mRNA alternative splicing, this findings was consistent with that of our previous study focused on the phosphorylation modification changes in the hippocampus of GF mice [30].…”
Section: Functional Analysis Of Differentially Expressed Proteins In the Absence Of Gut Microbiotasupporting
confidence: 92%
“…However, the exact effects of new genetic biomarkers, i.e., mmu-miR-465c-5p, mmu-miR-883b-3p, and mmu-miR-377-3p, on neurodevelopment needed to be further warranted. Consistently, our previous phosphoproteomics study indicated that axon guidance was the primary functional change shared among gut microbiota-dysbiosis-induced depression mice, stress-induced depression rats and MDD postmortem brains (Wang et al, 2020). Taken together, it is suggested that alterations in neurodevelopment, such as axonal guidance, neurogenesis and myelination, underlie the pathological mechanisms by which gut microbiota-dysbiosis induces depression in mice.…”
Section: Discussionsupporting
confidence: 77%
“…Gut microbiota can regulate depression via the microbiota-gut-brain axis ( Foster and McVey Neufeld, 2013 ). Previously, disruption to mitochondria-mediated biological processes, the MAPK pathway and the CAMKII-CREB pathway, and the hypothalamic-pituitary-adrenal (HPA) axis were identified in gut microbiota-dysbiosis depressed mice ( Li et al, 2018 ; Liu et al, 2020a ; Wang et al, 2020 ). Many pathways in the gut-brain axis, from intricate neuronal pathways to subtle small molecule messaging systems, are involved in the mechanisms by which gut microbiota dysbiosis causes depression-related brain dysfunction and behavioral changes ( Cryan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glutamatergic activity in the brain may be directly affected by the gut–brain axis. A recent study in mice used mass spectrometry of phosphorylation sites in hippocampus tissue to examine the gut–brain axis effects on the brain of depressive and control-type microbiota profiles [ 196 ]. The phosphorylation dysregulations were consistently associated with glutamatergic neurotransmitter disturbances.…”
Section: Effects Of Gut Microbiota On Cns Disorders and Glutamate Dys...mentioning
confidence: 99%